PREVALENCE AND DISTRIBUTION OF BLAST DISEASE (MAGNAPORTHE GRISEA) ON DIFFERENT COMPONENTS OF RICE PLANTS IN PADDY GROWING AREAS OF THE KASHMIR VALLEY - MOHD. SHAHIJAHAN DAR; SAJAD HUSSAIN; GH. NABI JOO; MASOOD MAJAZ (International Journal of Pharma and Bio Sciences, 2010)
All six districts of Kashmir viz; Anantnag, Budgam, Baramulla, Pulwama, Kupwara and Srinagar were selected in various paddy growing areas during kharif 2005 -2006 and 2007 and observations on prevalence and distribution of blast disease caused by Magnaporthe grisea were recorded. Maximum disease incidence 0f 25% and severity of 15% of nodal blast and maximum incidence 25% of most destructive phase- neck blast was recorded from the district Kupwara. Other components like rachis and glumes were also found highly infected with neck blast in district Kupwara.